'Zhonghua' tobacco advertisement in Shanghai: a descriptive study. Issue 5 (5th April 2013) - Zheng, PinPin; Ge, Xin; Qian, Haihong; Wang, Fan; Fu, Hua; Berg, Carla J; Kegler, Michelle C
Abstract : Objective: To document tobacco advertising practices of a popular, high-grade, domestic cigarette in China across a broad spectrum of channels. Methods: Media monitoring and direct observations were conducted to assess tobacco advertisements for Zhonghua cigarettes in Shanghai, China, through the following channels: newspapers, TV, internet, outdoor advertisements and point-of-sale advertisements. Results: Consistent with the national ban, no direct tobacco advertisements were found in newspapers or on TV. However, statements about counterfeit 'Zhonghua' cigarettes indirectly promoted Zhonghua tobacco through newspapers. Although no tobacco advertisements were found in Shanghai mainstream websites or in channels of national mainstream sites, a great amount of information was communicated about Zhonghua cigarettes via websites, using patriotic themes and associations with Chinese culture. Large outdoor tobacco advertisements of 'Loving my China' were found in downtown Shanghai. Zhonghua tobacco advertisements were present in almost all of the points-of-sale observed (95%). Conclusions: Zhonghua cigarettes are promoted directly and indirectly through a variety of channels. This study suggests there is an urgent need to establish comprehensive bans that prohibit all types of tobacco advertisements in China.